Pro Telerik ASP.NET and Silverlight controls : master Telerik controls for advanced ASP.NET and Silverlight projects - Paz, José Rolando Guay (Expert's voice in .NET., 2010)
This book provides a complete guide to implementing Telerik's range of ASP.NET and Silverlight controls. Telerik controls are invaluable for ASP.NET and Silverlight developers because they provide a vast array of rich controls targeted for the presentation layer of web applications. Telerik offers you solutions for the reports, grids, charts, and text-editing controls that you need but don't want to build from scratch yourself - the options are endless for increasing the functionality of any of your web solutions. What you'll learn * Understand how to integrate the standard Telerik controls in.